El Excentrico, 1967-09-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
September 20, 1967 [20 de septiembre de 1967]. No volume or issue number. Cover has photographs taken at the 16th of September celebration and portraits of models Alejandra Prez and Linda Muraira, both of whom have won Queen titles. The headline reads, "Pink Elephant Markets Extends congratulations to the Mexican - American community for the 16th of September Fiesta Celebration."